Selective δ-Opioid Receptor Agonist, KNT-127, Facilitates Contextual Fear Extinction via Infralimbic Cortex and Amygdala in Mice - Kawaminami, Ayako; Yamada, Daisuke; Yanagisawa, Shoko; Shirakata, Motoki; Iio, Keita; Nagase, Hiroshi; Saitoh, Akiyoshi (Frontiers in Behavioral Neuroscience, 2022)
Facilitation of fear extinction is a desirable action for the drugs to treat fear-related diseases, such as post-traumatic stress disorder. We previously reported that a selective agonist of the δ-opioid receptor (DOP), KNT-127, facilitates contextual fear extinction in mice. However, its site of action in the brain and the underlying molecular mechanism remains unknown. Here, we investigated brain regions and cellular signaling pathways that may mediate the action of KNT-127 on fear extinction. Twenty-four h after the fear conditioning, mice were re-exposed to the conditioning chamber for 6 min as extinction training (re-exposure 1). KNT-127 was microinjected into either the basolateral nucleus of the amygdala (BLA), hippocampus (HPC), prelimbic (PL), or infralimbic (IL) subregions of the medial prefrontal cortex, 30 min before re-exposure 1. Next day, mice were re-exposed to the chamber for 6 min as memory testing (re-exposure 2). KNT-127 infused into the BLA and IL, but not HPC or PL, significantly reduced the freezing response in re-exposure 2 compared with those of control. The effect of KNT-127 administered into the BLA and IL was antagonized by pretreatment with a selective DOP antagonist. Further, the effect of KNT-127 was abolished by local administration of MEK/ERK inhibitor into the BLA, and PI3K/Akt inhibitor into the IL, respectively. These results suggested that the effect of KNT-127 was mediated by MEK/ERK signaling in the BLA, PI3K/Akt signaling in the IL, and DOPs in both brain regions. Here, we propose that DOPs play a role in fear extinction via distinct signaling pathways in the BLA and IL.